Orthogonal Molecular Assembly: Eliminating Intrinsic Phonon Modes in Organic THz Generators - Kim, Seung Jun; Seok, Jin Hong; Yu, In Cheol; Lee, Jeong Hyeon; Kim, Won Tae; Shin, Bong Rim; Yoon, Ga Eun; Lee, Yun Sang; Kim, Jin Chul; Yoon, Woojin; Yun, Hoseop; Jazbinsek, Mojca; et al. (Advanced Optical Materials, 2022)
This work reports a series of new organic electro-optic salt crystals possessing unusual orthogonal dipole-coupling assembly that act as dimple-free THz generators. In the new crystals, optically anisotropic aromatic anions introducing highly electronegative fluorinated substituents are orthogonally assembled with optically anisotropic nonlinear optical benzothiazolium cations. These orthogonal cation–anion assembled crystals exhibit strong suppression of intrinsic THz phonon modes along the polar axis, which results in a wide THz absorption-free range from 1.5 to 4.0 THz without substantial absorption peaks. This is sharply in contrast to previous benchmark crystals with parallel cation–anion assembly; for example, in analogous crystals, several strong absorption peaks appear in this frequency range. This absence of strong absorption peaks is attributed to the orthogonal cation–anion dipole coupling assembly, the formation of fluorinate-induced strong interionic interactions, and a high packing ability of uniaxial anions. With top-level macroscopic optical nonlinearity, new orthogonal-dipole assembled crystals make dimple-free THz wave generation possible in the range of about 1.5–4.0 THz, which is very beneficial for characterizing signature peaks related to molecular phonon motions of analytes in THz spectroscopy. Therefore, orthogonal molecular assembly of optically highly anisotropic molecules provides an efficient way to substantially reduce and control intrinsic THz phonon modes.
Keywords: Absorption peaks; Cation-anions; Dipole coupling; Electro-optics; Molecular assembly; Organics; Orthogonal dipoles; Phonon mode; Salt crystals; Strong absorptions; electro-optics; nonlinear optics; optical anisotropy; phonons; terahertz waves